Handle with care: authorship challenges and conflicts in research publication - Kumar, Mahendra (International Journal Of Community Medicine And Public Health, 2024)
This review article explores how to determine correct authorship order, addresses disputes among co-authors over authorship credit, identifies misconduct, and offers recommendations to resolve such conflicts. An electronic literature search was conducted using keywords such as “authorship,” “authorship conflict,” “publication abuses” “co-authorship” and “co-authorship order,” among others. Over 100 free full-text articles published between 2010 and 2024 were reviewed. The review presents different perspectives of authorship disputes, how to decide the order of authorship, authorship abuse, and various types of scientific misconduct. Additionally, suggestions from various authorities on improving current authorship practices are included.